ТАЛАБАЛАРНИНГ УМУМКАСБИЙ ФАНЛАРИ БЎЙИЧА КАСБИЙ ТАЙЁРГАРЛИГИНИ ТАКОМИЛЛАШТИРИШ - Орынбетов, Н. (SCIENCE and SOCIETY, 2021)
Establishing and implementing electronic textbooks on independent learning in the process of distance learning is a vital task. E- learning resources are used to manage the learning process, to facilitate the student‘s work in teaching, and to monitor and evaluate basic knowledge. The main purpose of these tecniques is to develop knowledge and skills in this field of teaching.